Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3906/bot-1304-32
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of Chlorella-related chlorophytes (Chlorophyta) from Anatolian freshwaters of Turkey

Abstract: IntroductionMany coccoid algae are very difficult to identify because of their extremely small size and simple morphology, and they have been referred to as "little green balls" (Callieri and Stockner, 2002). These little green balls have often been reported as Chlorella Beijerinck or Chlorella vulgaris Beijerinck (Fawley et al., 2004). Since C. vulgaris "Beijerinck strain" (SAG 211-11b) was first described and isolated in axenic culture about 120 years ago, Chlorella strains have been used as model organisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…The microscopic observations of this work are in agreement with those recorded for the genus Chlorella Beijerinck [ 4 , 45 ]. The phylogenetic analyses resulted in a topology presenting unrooted tree that illustrates the relatedness of the leaf nodes and reflects the branching order without making assumptions about common ancestry [ 43 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The microscopic observations of this work are in agreement with those recorded for the genus Chlorella Beijerinck [ 4 , 45 ]. The phylogenetic analyses resulted in a topology presenting unrooted tree that illustrates the relatedness of the leaf nodes and reflects the branching order without making assumptions about common ancestry [ 43 ].…”
Section: Discussionsupporting
confidence: 90%
“…Screening of local microalgae species with high nutritional value and potential for oil production is essential to achieve successful commercial large-scale cultures. The species of the genus Chlorella are considered as cryptic species that are morphologically similar but genetically distinct [ 3 , 4 ]. The lack of obvious morphological taxonomic characteristics in addition to an exclusively asexual reproductive cycle by means of autospores makes it difficult to differentiate between the species of the genus Chlorella Beijerinck depending on the traditional taxonomy [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…, Baytut et al. ) the Watanabea clade primarily encompasses algae of subaerial habitats, with some taxa described from specialized environments of low pH (e.g., Viridiella ; Albertano et al. , Huss et al.…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts have been made to distinguish among these species. Baytut et al (2014) and Hirooka et al (2014) showed that the type strain P. pringsheimii was separated from the closely related C. vulgaris and C. sorokiniana strains depending on the sequences of 18S rDNA and chloroplast 16S rDNA regions. However, other species await phylogenetic separation until new taxonomic markers can distinguish their classification.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the classification of the elliptical coccoid and spherical forms was reconsidered due to insufficient morphological differentiation. Physiological, molecular and biochemical investigations were performed to revise the taxonomy of the species belonging to ''Chlorella'' (Darienko et al 2010;Görs et al 2010;Baytut et al 2014;Heeg and Wolf 2015).…”
Section: Introductionmentioning
confidence: 99%